Factors Affecting the Academic Performance of Grade 12 ABM Working Students in Bestlink College of the Philippines S.Y. 2018-2019 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The term "working students" does not seem to elicit sympathetic feelings anymore. It may be because that was the typical mindset of the people to the working students. In a country like the Philippines, people think that all working students belong to a poor family, but poverty is not the only qualification to be a working student. One needs to be determined and possess a strong personality to face the challenge. This research used a descriptive method to determine the factors affecting the academic performance of working students. The researchers used questionnaires distributed to 50 selected Grade 12 ABM working students. The data gathered were analyzed and interpreted in the entire study. One of the reasons why students need to work while studying is because of the increasing school expenses and to help their parents as well. Students cannot manage their time so their school performance was affected too. From the studies done, the researchers understand that the lives of working students are not easy. They encountered a lot of challenges and problems, unlike the non-working students. Since the purpose of the study is to determine the problems encountered by working students, the researchers found out that the life of working students in school is not easy. They must be strong, stand on their own, and be responsible to survive and to help their family.
Keywords: financial problem, working students, school expenses, challenges